First Resistance Mechanisms Characterization in Glyphosate-Resistant Leptochloa virgata - Alcántara-de la Cruz, Ricardo; Rojano-Delgado, Antonia M.; Giménez, María J.; Cruz-Hipolito, Hugo E.; Domínguez-Valenzuela, José A.; Barro, Francisco; De Prado, Rafael (Frontiers in Plant Science, 2016)
Leptochloa virgata (L.) P. Beauv. is an annual weed common in citrus groves in the states of Puebla and Veracruz, Mexico limiting their production. Since 2010, several L. virgata populations were identified as being resistant to glyphosate, but studies of their resistance mechanisms developed by this species have been conducted. In this work, three glyphosate-resistant populations (R8, R14 and R15) collected in citrus orchards from Mexico, were used to study their resistance mechanisms comparing them to one susceptible population (S). Dose-response and shikimic acid accumulation assays confirmed the glyphosate resistance of the three resistant populations. Higher doses of up to 720 g ae ha-1 (field dose) were needed to control by 50% plants of resistant populations. The S population absorbed between 7 and 13% more 14C-glyphosate than resistant ones, and translocated up to 32.2% of 14C-glyphosate to the roots at 96 h after treatment (HAT). The R8, R14 and R15 populations translocated only 24.5, 26.5 and 21.9%, respectively. The enzyme activity of 5-enolpyruvyl shikimate-3-phosphate synthase (EPSPS) was not different in the S, R8 and R14 populations. The R15 Population exhibited 165.9 times greater EPSPS activity. Additionally, this population showed a higher EPSPS basal activity and a substitution in the codon 106 from Proline to Serine in the EPSPS protein sequence. EPSPS gene expression in the R15 population was similar to that of S population. In conclusion, the three resistant L. virgata populations show reduced absorption and translocation of 14C-glyphosate. Moreover, a mutation and an enhanced EPSPS basal activity at target-site level confers higher resistance to glyphosate. These results describe for the first time the glyphosate resistance mechanisms developed by resistant L. virgata populations of citrus orchards from Mexico.